The Correlation between Reading Strategies and Reading Comprehension - Manurung, Sulastri; Ariyanti, Anita; Yana, Dewi; Sinaga, Juwita Boneka; Adam, Adam (CAHAYA PENDIDIKAN, 2023)
Indonesian students continue encounter difficulties when it comes to reading English academic materials as English is their foreign language. The study aims to explore the reading strategies employed by English as a Foreign Language (EFL) students in order to improve their reading comprehension and to determine whether a significant correlation exists between reading strategies and reading comprehension. The study involved 60 participants from one senior high school in Batam, Indonesia. The study utilized Survey of Reading Strategies (SORS) and reading comprehension test. The Kolmogorov-Smirnov test was performed to determine the normality of the data distribution while Pearson correlation was utilized to investigate the interrelation among the variables. The results showed that students most commonly employed problem-solving strategies when reading and there was a significant correlation between reading strategy and reading comprehension. The findings suggest that students who employ a variety of reading strategies, including problem-solving strategies, support reading strategies, and global reading strategies, perform better on reading comprehension assessments. The study made a significant addition to the field of English language teaching by highlighting the need of raising EFL students’ awareness and teaching them proper reading strategy for comprehending scholarly texts.